Non-porous organic crystals and their interaction with guest molecules from the gas phase - Casco, Mirian Elizabeth; Krupp, Felix; Grätz, Sven (Dr. rer. nat.); Schwenger, Alexander (Dr. rer. nat.); Damakoudi, Vassiliki; Richert, Clemens (Prof. Dr. sc. nat., Dr. hum. biol.); Frey, Wolfgang (Dr. rer. nat.); Borchardt, Lars (Prof. Dr. Dr. rer. nat.) (2020)
Some organic molecules encapsulate solvents upon crystallization. One class of compounds that shows a high propensity to form such crystalline solvates are tetraaryladamantanes (TAAs). Recently, tetrakis(dialkoxyphenyl)-adamantanes have been shown to encapsulate a wide range of guest molecules in their crystals, and to stabilize the guest molecules against undesired reactions. The term ‘encapsulating organic crystals’ (EnOCs) has been coined for these species. In this work, we studied the behavior of three TAAs upon exposition to different guest molecules by means of sorption technique. We firstly measured the vapor adsorption/desorption isotherms with water, tetrahydrofuran and toluene, and secondly, we studied the uptake of methane on dry and wet TAAs. Uptake of methane beyond one molar equivalent was detected for wet crystals, even though the materials showed a lack of porosity. Thus far, such behavior, which we ascribe to methane hydrate formation, had been described for porous non-crystalline materials or crystals with detectable porosity, not for non-porous organic crystals. Our results show that TAA crystals have interesting properties beyond the formation of conventional solvates. Gas-containing organic crystals may find application as reservoirs for gases that are difficult to encapsulate or are slow to form crystalline hydrates in the absence of a host compound. Wet tetraaryladamantane crystals take up methane in form of methane hydrate structure I, even though they appear non-porous to argon.